Jaringan Ulama Pesantren dan Transformasi Sosial Keagamaan di Nusantara: Perspektif ‘Ashabiyah Ibn Khaldun dan Teori Strukturasi Anthony Giddens - Ahmad Jazuli; Moh Fadil; Nimatuz Zuhro (Lembaga Yasin AlSys, 2026)
The network of pesantren ulama is a dynamic socio-religious phenomenon because it plays a role in maintaining scholarly continuity, strengthening social solidarity, and responding to changes in social structure within the pesantren system in the Nusantara. This study aimed to examine the network of pesantren ulama by highlighting the role of social solidarity (‘ashabiyah) and changes in social structure within the pesantren tradition. This study used a qualitative approach with a library research method. Data were collected from various relevant primary and secondary sources and were then analyzed using content analysis and thematic analysis techniques. The results showed that the network of pesantren ulama was formed through mechanisms of scholarly transmission chains, intellectual mobility, and the tradition of teaching kitab kuning, which continuously strengthened social and intellectual attachment. This network was maintained through everyday social practices and developed through educational modernization and the use of digital technology. These findings confirm that the sustainability of ulama networks is supported by strong social solidarity and the process of structural reproduction, while the ability to adapt becomes an important factor in facing social change. Theoretically, this study contributes to the development of Islamic sociology studies, while practically it can serve as a basis for formulating pesantren education policies that are more responsive to contemporary developments.